Feline gut microbiota composition in association with feline coronavirus infection: A pilot study - Meazzi, Sara; Stranieri, Angelica; Lauzi, Stefania; Bonsembiante, Federico; Ferro, Silvia; Paltrinieri, Saverio; Giordano, Alessia (Research in veterinary science, 2019)
Feline coronaviruses (FCoV) colonize the intestinal tract, however, due to not fully understood mutations, they can spread systemically and cause feline infectious peritonitis (FIP). Recent studies on human medicine report that gut microbiota is involved in the development of systemic disorders and could influence the immune response to viral diseases. The aim of this study was to provide preliminary data on the fecal microbiota composition in healthy cats compared to FCoV-infected cats, with and without FIP. Cats were equally grouped as healthy FCoV-negative, healthy FCoV-positive or FIP affected (total n = 15). Fecal sample were evaluated for the microbiota composition. A total of 3,231,916 sequences were analyzed. The samples' alpha-diversity curves did not reach a proper plateau and, for the beta-diversity, the samples seemed not to group perfectly by category, even if the healthy FCoV-positive group showed a hybrid microbial composition between FCoV-negative and FIP groups. Although there were no taxa significantly linked to the different conditions, some peculiar patterns were recognized: Firmicutes was always the most represented phylum, followed by Bacteroidetes and Actinobacteria. In FCoV-positive cats, the Firmicutes and Bacteroidetes were respectively over- and under-represented, compared to the other groups. Among FIP cats, three subjects shared a similar microbiome, one cat showed a different microbial profile and the other one had the lowest number of diverse phyla. Despite the limited number of animals, some differences in the fecal microbiome between the groups were observed, suggesting to further investigate the possible correlation between gut microbiota and FCoV infection in cats. •Mutated form of enteric feline coronaviruses (FCoV) may spread systemically inducing feline infectious peritonitis (FIP).•Gut microbiota is known to be influenced by viral diseases in people and in some animal species.•Fecal microbiota was evaluated in 15 cats divided in three groups as healthy, positive to FCoV and affected by FIP.•Some microbiota peculiarities have been observed associated with the presence of coronavirus and/or disease.•Feline gut microbiota composition may be associated with FCoV infection and thus need to be further investigated.